Clinical Microbiology Perspective of Empyema caused by Streptococcus constellatus in Malignancy Patient: A Case Report - Agung Dewi Sekar; Rosantia Sarassari; Soedarsono Soedarsono; Kuntaman Kuntaman (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Streptococcus constellatus (SC) is commensal bacteria and belongs to Streptococcus anginosus group (SAG). However, SC causes infections especially in patient with underlying diseases. SC empyema is a clinical case that is described in very few studies, especially in Indonesia.Case: A 45-year-old man was admitted to emergency department in Dr. Soetomo General Hospital Surabaya with respiratory insufficiency on November 11th 2020 after 3 months of non-productive cough and a week of weakness. He was diagnosed with empyema on right hemithorax and received chest tube insertion. SC was isolated from pleural fluid sample after first day of culture on Bactec BD bottle. GeneXpert result of pleural fluid was negative for Mycobacterium tuberculosis (MTB). He completed 10 days of intravenous ampicillin-sulbactam and metronidazole. The CT scan reported solid mass of 4.7x7.4x7.8 cm in posterolateral segment of inferior lobe right lung, right pleural effusion, with adenocarcinoma as biopsy result.Discussion: SC is a normal commensal in respiratory tract, however with the presence of a certain factor such as immunocompromised, colonized SAG directly induces an infection after entering normal sterile sites in the body including pleural fluid.Conclusion: Although infection caused by SC is a rare case, it still should be considered in clinical diagnosis and treatment of related infections, particularly in patients with comorbidities. The prognosis was good with appropriate antibiotics and chest tube insertion.